Multi-pulse thermoreflectance imaging with structure function analyses for measuring thermophysical properties of microscale heterostructures - Liu, Zhao-Yang; Liu, Zhi-Ke; Yang, Guang; Cao, Bing-Yang (International journal of heat and mass transfer, 2024)
•A multi-pulse thermoreflectance thermal imaging (TTI) with a 50 ns temporal resolution is utilized combining with structure function algorithm.•The proposed scheme can simultaneously measure thermophysical properties in microscale heterostructures.•The proposed scheme achieves synchronous sensitivities to multiple parameters and eliminates the reliance on reference samples.•Experiments on a microscale Silicon-on-Insulator (SOI) sample exhibit a relative error of <10% compared to references. The thermophysical properties of nano/microscale heterostructures play a crucial role in the performance and reliability of electronics. However, existing measurements encounter several challenges, including detecting multiple parameters synchronously and reliance on reference samples etc. In this study, we propose a multi-pulse thermoreflectance thermal imaging (TTI) combining with structure function algorithm, achieving simultaneous measurement of the thermal conductivities, specific heat capacities, and thermal boundary resistances (TBRs) of microscale heterostructures. A non-iterative methodology is established and the singular model parameter is evaluated through transient heat conduction modeling. We delineate criteria for thermal transient testing and achieve high-precision measurements over a broad time range by employing a multi-pulse strategy with a TTI system with a 50 ns temporal resolution. Our experimental measurements on a microscale Silicon-on-Insulator (SOI) sample validate the method's effectiveness. The measured thermophysical properties, including thermal conductivities of the device layer and handle wafer, TBR, and specific heat capacity of the device layer, exhibit a relative error of <10% compared to prior studies. Our approach presents an effective solution for precise thermal characterization within modern electronic devices.